Safety and Pharmacokinetics of Monoclonal Antibodies VRC07-523LS and PGT121 Administered Subcutaneously for Human Immunodeficiency Virus Prevention. (4th February 2022) - Mahomed, Sharana; Garrett, Nigel; Capparelli, Edmund V; Osman, Farzana; Harkoo, Ishana; Yende-Zuma, Nonhlanhla; Gengiah, Tanuja N; Archary, Derseree; Samsunder, Natasha; Baxter, Cheryl; Mkhize, Nonhlanhla N; Modise, Tandile; et al.
Abstract: Background: Effective, long-acting prevention approaches are needed to reduce human immunodeficiency virus (HIV) incidence. We evaluated the safety and pharmacokinetics of VRC07-523LS and PGT121 administered subcutaneously alone and in combination as passive immunization for young women in South Africa. Methods: CAPRISA 012A was a randomized, double-blinded, placebo-controlled, dose-escalation phase 1 trial. We enrolled 45 HIV-negative women into 9 groups and assessed safety, tolerability, pharmacokinetics, neutralization activity, and antidrug antibody levels. Pharmacokinetic modeling was conducted to predict steady-state concentrations for 12- and 24-weekly dosing intervals. Results: VRC07-523LS and PGT121, administered subcutaneously, were safe and well tolerated. Most common reactogenicity events were injection site tenderness and headaches. Nine product-related adverse events were mild and transient. Median VRC07-523LS concentrations after 20 mg/kg doses were 9.65 μg/mL and 3.86 μg/mL at 16 and 24 weeks. The median week 8 concentration after the 10 mg/kg PGT121 dose was 8.26 μg/mL. Modeling of PGT121 at 20 mg/kg showed median concentrations of 1.37 μg/mL and 0.22 μg/mL at 16 and 24 weeks. Half-lives of VRC07-523LS and PGT121 were 29 and 20 days. Both antibodies retained neutralizing activity postadministration and no antidrug antibodies were detected. Conclusions: Subcutaneous administration of VRC07-523LS in combination with optimized versions of PGT121 or other antibodies should be further assessed for HIV prevention. Abstract : VRC07-523LS and PGT121 were safe and well tolerated with detectable serum antibody concentrations. Subcutaneous administration of VRC07-523LS in combination with optimized versions of PGT121 or other antibodies should be further assessed for HIV prevention.